General Principles for the Detection of Modified Nucleotides in RNA by Specific Reagents. Issue 10 (17th September 2021) - Helm, Mark; Schmidt‐Dengler, Martina C.; Weber, Marlies; Motorin, Yuri
Abstract: Epitranscriptomics heavily rely on chemical reagents for the detection, quantification, and localization of modified nucleotides in transcriptomes. Recent years have seen a surge in mapping methods that use innovative and rediscovered organic chemistry in high throughput approaches. While this has brought about a leap of progress in this young field, it has also become clear that the different chemistries feature variegated specificity and selectivity. The associated error rates, e.g., in terms of false positives and false negatives, are in large part inherent to the chemistry employed. This means that even assuming technically perfect execution, the interpretation of mapping results issuing from the application of such chemistries are limited by intrinsic features of chemical reactivity. An important but often ignored fact is that the huge stochiometric excess of unmodified over‐modified nucleotides is not inert to any of the reagents employed. Consequently, any reaction aimed at chemical discrimination of modified versus unmodified nucleotides has optimal conditions for selectivity that are ultimately anchored in relative reaction rates, whose ratio imposes intrinsic limits to selectivity. Here chemical reactivities of canonical and modified ribonucleosides are revisited as a basis for an understanding of the limits of selectivity achievable with chemical methods. Abstract : Epitranscriptomic (RNA modification) analysis by high throughput approaches heavily relies on chemical reagents used for the detection, quantification, and localization of modifications. Such modified residues differ from their unmodified counterparts by reactivity toward specific chemicals. Here chemical reactivities of canonical and modified ribonucleosides are revisited as a basis for an understanding of the limits of selectivity achievable with chemical methods.